GEOGEBRA IN ACTION: ENHANCING PROBLEM SOLVING IN ALGEBRA THROUGH DYNAMIC MATHEMATICS SOFTWARE - Naharia Safitri; Ali Shodikin; Ismail Ismail (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Mathematics learning in junior high schools often faces challenges in developing algebraic problem-solving skills because the concepts are abstract and symbolic. This study investigates the impact of GeoGebra on junior high school students' algebraic problem-solving skills, analyzed through Polya's problem-solving stages. The research method used is qualitative with a case study approach on two eighth-grade students. Data were collected through observations, interviews, and analysis of student work documents, both before and after using GeoGebra. The results showed that with conventional methods, students could solve the problem correctly, but only part of the Polya stages were achieved and the rest were not written in full. Meanwhile, the use of GeoGebra allows students to display all stages of Polya in a more systematic and structured manner, from understanding the problem to re-examining the solution. GeoGebra also provides visualization in the form of images, which increases student engagement and understanding of algebraic concepts. Thus, GeoGebra effectively improved junior high school students' problem-solving skills.